Moderation in Islam: A Comparative Case Study on Perception of International Students in Malaysia - Mansoureh Ebrahimi; Kamaruzaman Yusoff; Arieff Salleh Bin Rosman (Journal of Islamic Thought and Civilization, 2022)
Moderation in Islam was defined by Holy Prophet Mohammad (PBUH) as the ‘Way of Islam’. He has emphasized on opening a man’s heart to communal welfare and peace by avoiding scepticism. Moderation reifies faith, rejects extremism, and paves all roads to peaceful conflict resolution. Islamic moderation balances democratic social development in the face of restraints and boundaries to purchase sustainable peace. However, some schools of thought that appeal to Middle East and African Muslims hold forth the extremist ideology that has tarnished Islam globally. They ignore fundamental Islamic principles and archetypal Muslim characteristics thus they completely ignore Islam’s path of moderation. This study compares thoughts on Islamic moderation from the West Asian students (WAS) with the rest of Asian students (AS) studying in Malaysia. Using qualitative and quantitative approaches, we have tried to achieve research objectives and found that WAS understood less of Islamic moderation than did the students from the rest of Asia. The Chi-square statistic was used to critically test the unique results of this study. The overall findings have revealed bigoted and negative WAS opinions towards Islamic moderation as well as towards non-Muslim societies. The Chauvinism appeared to be consequent to Arab permeated cultures and indoctrinations. Such perceptions and ignorance of authentic Islam affects the entire world with deeply negative overtones.